KELAYAKAN TEORETIS MODEL STRUKTUR ORGANELA SEL DARI BAHAN ADONAN TEPUNG SEBAGAI MEDIA PEMBELAJARAN KELAS XI SMA - PRISKALA LEORUSLINA (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2014)
The learning process requires media that helps in understanding the concept in this topic of matter. To learn cel’s organelles requires more than simply memorizing it need variation in the learning process. One of these variations to using a medium of learning. The purpose of this research is to produce a model of cell’s organelles. This research intends to knows the theoretical viable of organelles cell model that was make from XIth grade student mix flour dough as a learning medium. The developing model was make use of ASSURE development procedure. The research instrument used one validation sheet. The results showed that this is theoretically high viable as much as 92%. Keywords: media, model, organelles cell